Enhancing the sustainability and competitiveness of Islamic Banking: a comparative study of fiscal policy and regulatory Frameworks in Indonesia and Malaysia - Didih Muhamad Sudi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
The rapid global expansion of Islamic banking urgently necessitates robust fiscal policies and regulatory frameworks, particularly in leading Muslim-majority economies like Indonesia and Malaysia, where their long-term sustainability and competitiveness are critically dependent on effective governance. This study addresses a critical gap by providing an in-depth comparative analysis of the fiscal policy and regulatory frameworks in enhancing the sustainability and competitiveness of Islamic banking in these two countries, focusing on underlying issues that justify this comparison. Employing a qualitative, interpretivist comparative case study approach, data were collected through comprehensive literature reviews, in-depth analysis of key policy documents (Indonesia’s Law No. 21 of 2008 on Islamic Banking, Malaysia’s Islamic Financial Services Act 2013), and secondary data from financial authorities. Thematic content analysis was used to compare their approaches systematically. The findings reveal that both countries have strategically employed tax incentives, liquidity measures, and legal oversight to foster sectoral growth. Indonesia with a multi-agency framework, rooted in Law No. 21 of 2008, demonstrates a strong commitment to Islamic principles but grapples with regulatory overlaps and operational inefficiencies. Malaysia with centralized approach, anchored by the Islamic Financial Services Act 2013 and guided by the Shariah Advisory Council, has contributed to global competitiveness. The findings also highlight key policy challenges, including regulatory fragmentation, Shariah compliance in fintech integration, and limited technical capacity, and offer actionable recommendations to strengthen financial inclusion, institutional resilience, and the long-term sustainability of Islamic banking in both jurisdictions.